Wastewater Irrigation and Soil Contamination Effect on Some Leafy Vegetables Grown in Syrian Aleppo City - AZIZ RAMADAN, ABDUL; MANDIL, HASNA (Asian Journal of Chemistry, 2010)
The accumulation effect of contaminated soil and wastewater irrigation on the concentration of the following elements: As, Pb, Cd, Cr, Ni, Cu, Zn and Mn on some leafy vegetables grown in Syrian Aleppo City by atomic absorption spectrometry have been carried out. The following leafy vegetables: mint, parsley, mallow, spinach, endive and cress were investigated. Four different models (I-IV) of leafy vegetables were applied as follows: both contaminated soil and irrigation water, uncontaminated soil and irrigation by contaminated water, contaminated soil and irrigation by uncontaminated water and finally both uncontaminated soil and irrigation water. As the result of first important model based on both contaminated soil and wastewater irrigation, the measured concentration range of the investigating elements was as follows: As: 7.82 to 1.31; Pb: 8.73 to 2.12; Cd: 1.81 to 0.83; Cr: 2.40 to 1.16; Ni: 3.53 to 2.11; Cu: 10.80 to 6.02; Zn: 22.3 to 9.81 and Mn: 32.5 to 15.5 ppm which is the highest concentrations among the other 3 models. According to the data of daily intake of metals, DIM the toxic level values of Cd, As and Pb elements in mint, mallow and parsley were more than the recommended maximum tolerable levels proposed by the FAO/WHO which is a serious indication to a health hazard for human consumption.